Analisis Kepuasan Pelanggan di Metro Musik Malang Menggunakan Metode SERVQUAL, IPA, dan QFD - Andana Haris Goenawan; Yurida Ekawati (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2021)
Metro Musik is a well-known music equipment store in Malang City that also provides music education services. This service quality research was conducted because Metro Musik assessed that the decline in business was not only caused by the pandemic but also by customer dissatisfaction with the services provided by Metro Musik, based on criticism from buyers about the quality of service at Metro Musik Malang. This study aims to identify service quality using the Servqual method, prioritize service quality improvements using the Importance Performance Analysis (IPA) method, propose improvements using the Quality Function Deployment (QFD) method to improve service quality, and measure service quality at Metro Musik Malang after improvement efforts have been implemented. Based on the GAP 5 calculation, it was found that none of the attributes met customer expectations, or the quality of service at Metro Musik Malang was considered inadequate. Then, based on the IPA analysis, four attributes were prioritized, namely attributes number 2, 8, 10, and 11. Five improvements were proposed for the four prioritized attributes, including training employees to be more responsive in serving customers, creating reminders with detailed schedules, displaying realistic product photos, explaining corresponding product specifications, planning to add 1 to 2 employees, and renovating the store. However, only three out of the five proposals were implemented. The results of the implementation provided a 35% increase in customer satisfaction with the quality of service at Metro Musik Malang. Attributes number 2, 8, and 10 experienced an increase in customer satisfaction, but attribute number 11 experienced a decrease.